Dynamics of Family Role Structure in Consumer Behaviour - Kakati, Rinalini Pathak; Ahmed, Shazeed (Indian Journal of Marketing, 2016)
A family is an important constituent of consumers as a buying unit within a society. It is regarded as one of the most influential primary reference groups. In India, a nuclear family comprised almost of 63% of all families in 2009. As per the Population Projection for India 2001-26 by Census of India, rural Indian population comprised of 70% of the total population in 2011, where the average family size was five members per household. Different members of a family play different roles in family buying decisions, and the degree of influence is also varied. This paper tried to investigate how different members of a family influenced purchase decisions in a family with respect to purchases of FMCGs and consumer durables. The study is a combination of exploratory and descriptive research conducted in two prominent districts namely, Kamrup and Tinsukia of North East India. In the FMCG sector, the study found that in the two districts, both husbands and elderly persons played an equally significant role. Furthermore, wives basically played the role of a homemaker and had a minor role as influencer. Majority of the goods purchased were for the family consumption. In the durables sector, the study found that the financer is the decider who happened to be the husband in both the districts. The husband was also seen playing the role of a purchaser. On the other hand, wives played the role of an initiator, influencer, decider, and purchaser in a major way. Furthermore, elderly persons played the role of an influencer. Lastly, children played a major role as an initiator and a minor role as an influencer in purchases.